2005
DOI: 10.1111/j.1365-2222.2005.02141.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic diseases and asthma in relation to serum immunoglobulins and salivary immunoglobulin A in pre‐school children: a follow‐up community‐based study

Abstract: Allergic manifestations in predisposed children may be influenced by the rate of maturation of immunological components that counteract sensitization or inhibit effector mechanisms of allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 36 publications
4
40
1
1
Order By: Relevance
“…These results are consistent with those of previous studies [2,4-6,10] showing that low IgA level is associated with atopic disease. The subjects of previous studies [2,4-6] were mainly children, and some authors have found that the atopy/IgA relationship was unclear in adult patients [7]. However, a study in adult patients by Balzar et al [10] revealed a relationship between serum IgA level and asthma severity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with those of previous studies [2,4-6,10] showing that low IgA level is associated with atopic disease. The subjects of previous studies [2,4-6] were mainly children, and some authors have found that the atopy/IgA relationship was unclear in adult patients [7]. However, a study in adult patients by Balzar et al [10] revealed a relationship between serum IgA level and asthma severity.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, infants born to atopic parents had a higher prevalence of salivary IgA deficiency [5]; children with positive skin prick tests to common allergens had lower serum IgA levels; and children who developed allergic rhinitis or atopic eczema had lower salivary IgA levels [6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated IgE and IgA levels in the BALF of T-bet Ϫ/Ϫ mice likely reflect persistent stimulation of the respiratory mucosa by M. pulmonis. Elevated IgA levels also are associated with the asthmatic phenotype and AHR (50,51). IgG2b Abs play a major role in the clearance of M. pulmonis, and failure to mount an IgG2b response is associated with increased disease susceptibility (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Low sIgA have been associated with atopic eczema (13). In children with chronic airways diseases there was only a slight increase of secretory IgA during the first 4 years of live (14).…”
Section: Introductionmentioning
confidence: 99%